Job satisfaction and its relationship to sports talent management in the administrative bodies of the sub-federations of handball in Iraq - حسن, م.د. بسام عبد الحمزة (Sulaimani Journal for Humanities, 2026)
Given the clear interest among writers and management professionals in the topic of employee efficiency within organizations and the extent to which these employees can exert their best efforts and capabilities for the organization's success and growth, employment within the organization must be driven by employee enthusiasm and desire. This is essential for both retention and increased efficiency. In other words, individuals must be satisfied with their roles and responsibilities to be able to contribute their full potential. Job satisfaction acts as a motivator and incentive for giving back. The more satisfied employees are with their roles and responsibilities within their organizations, the greater their ability to manage athletic talent, leading to creativity and innovation in their work. Sports organizations, in particular, are among the most influential and impactful institutions in society, as sports and management are catalysts for development. Working with athletes necessitates the use of creative methods and approaches in sports management to ensure success and achieve optimal results. Hence, the importance of this research.
Keywords: Job satisfaction; Sports talent management; Subhandball federations